Seafood safety : a matter of any concern? - C.E.M. Bernardi (Università degli Studi di Milano, 2009)
SEAFOOD SAFETY: A MATTER OF ANY CONCERN ? Determination of Carbon Monoxide in Tuna by Gas Chromatography with Micro-Thermal Conductivity Detector. The suitability of a portable gas chromatograph equipped with a micro-thermal conductivity detector for the head-space determination of carbon monoxide (CO) in tuna samples is evaluated. Preliminary study on prevalence of larvae of Anisakidae family in European sea bass (Dicentrarchus labrax). A total of 561 fresh European sea bass from North-East Atlantic ocean were examined for Anisakidae larvae detection. It is the first record on the prevalence of Anisakidae larvae in this fish specie. An unexpected high prevalence was found. The results have an important consequence on epidemiology of anisakidosis and public health risk assessment. A case study: shelf-life of smoked herring fillets by volatile compounds analysis. Two different products of vacuum packed cold smoked herrings were analyzed at time intervals in order to evaluate the efficiency of the processing and product stability. Microbiological total counts, lactic acid bacteria, total coliforms, pH, water activity, water content, salt content (WPS) were determined. Shelf-life of vacuum packed cold-smoked salmon from italian market. Fourteen samples of different vacuum packed cold smoked salmon products purchased in Italian retail were analysed at about half shelf-life and at the expiry date. On the expiry date 12 samples were above the limits. Levels of Enterobacteriaceae and coagulase-positive staphylococci were very low, and no potential pathogenic bacteria were detected.